The process of adaptability and flexibility of floating house (Rumah Lanting) in West Kalimantan, Indonesia - Putro, J D; Zain, Z (ASCEE, 2022)
The culture of settlement of each person is different in accordance with internal and external factors. The culture of settling alongside the river such as in floating houses has becomes a local wisdom for the local community. The ability to adapt and make adjustments to the physical environment by floating house occupants makes this settlement exist until today. The concept of adaptation and adjustment to the physical environment becomes an important point for floating house occupants. Therefore, this study seeks to formulate the concept of adaptability and flexibility in floating houses. The research method used is the case study method with a multi-case approach. The selected cases are samples that indicate that there has been an adaptation process based on consideration of the duration of occupying the floating house. The analysis is carried out by looking at the patterns of occupants’ behavior that affect the function and nature of space. The results of this study are formulated into the concept of adaptation through two types of modification namely environmental modification and User modification. Environmental modification occurs when the function of the existing space changes, following the addition of property. User modification occurs when changes in spatial functions force the occupants to change behavioral patterns.